1998
DOI: 10.1175/1520-0434(1998)013<0852:tootis>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Tornadoes in Supercells Interacting with Boundaries during VORTEX-95

Abstract: During the Verifications of the Origins of Rotation in Tornadoes Experiment, nearly 70% of the significant tornadoes occurred near low-level boundaries not associated with the forward or rear flank downdrafts of supercells. In general, these were preexisting boundaries readily identified using conventional data sources. Most of the tornadoes occurred on the cool side of these low-level boundaries and generally within 30 km of the boundaries. It is likely that the low-level boundaries augmented the ''ambient'' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
102
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 24 publications
12
102
3
Order By: Relevance
“…This horizontal vorticity can then be tilted into the vertical and stretched by the updraft, and have the same effects on updraft intensity as described in the nonlinear pressure perturbation discussion above (e.g., Houze 1993;Markowski et al 1998;Rasmussen et al 2000).…”
Section: (Iv) Dynamic Pressure Perturbationsmentioning
confidence: 83%
See 1 more Smart Citation
“…This horizontal vorticity can then be tilted into the vertical and stretched by the updraft, and have the same effects on updraft intensity as described in the nonlinear pressure perturbation discussion above (e.g., Houze 1993;Markowski et al 1998;Rasmussen et al 2000).…”
Section: (Iv) Dynamic Pressure Perturbationsmentioning
confidence: 83%
“…Strong mid to upper-level storm-relative winds transport hydrometeors formed in the updraft sufficiently far downstream from the updraft that they fall toward the ground outside of the updraft region, and thus reduce the amount of water loading in the updraft. Conversely, when mid to upper-level stormrelative winds are weak, hydrometeors formed in the updraft remain in the updraft region, thereby increasing the degree of water loading in the updraft (e.g., Brooks et al 1994b;Rasmussen and Straka 1998). Thus, strong storm-relative winds at mid to upperlevels favor stronger updrafts through a reduction of water loading.…”
Section: ) Calculation Of Meteorological Parametersmentioning
confidence: 99%
“…Airmass boundaries are not only relatively easy to target; there is also substantial evidence that they can have a significant impact on a number of mesoscale processes/phenomena: for example, deep convection initiation [refer to the review of Weckwerth and Parsons (2006)], deep convection maintenance/ propagation (e.g., Newton 1963;Weaver 1979;Weaver and Nelson 1982;Wilhelmson and Chen 1982;Atkins et al 1999;Wilhelmson 2007a, 2012), | and tornadogenesis (e.g., Purdom 1976;Maddox et al 1980;Simpson et al 1986;Wilson and Schreiber 1986;Purdom 1993;Lee and Wilhelmson 1997;Markowski et al 1998;Rasmussen et al 2000;Caruso and Davies 2005;Houston and Wilhelmson 2007b), among many others. However, to understand the impact of airmass boundaries on these processes/phenomena requires data that UAS can, perhaps uniquely, collect.…”
Section: Experiments Design Mesoscale Targetsmentioning
confidence: 99%
“…This mechanism promotes the longlived updrafts of supercells which are able to transition to more stable inflow environments Goff (1975);Fankhauser (1982); Wakimoto (1982) which would otherwise weaken multicell storms (Ziegler et al 2010). In the absence of ambient horizontal vorticity within the convective environment, parcels sourced from more sheared low-level boundaries and local circulations can provide sufficient horizontal vorticity to promote supercell growth (Markowski et al 1998;Atkins et al 1999). Examples of these processes can be found throughout the literature.…”
Section: Storm-generated Effectsmentioning
confidence: 99%
“…Weisman and Klemp (1982) showed that for a given amount of buoyancy, a low-to-moderate shear noted for these events favours multicellular growth, rather than supercellular. The vorticity required to build a mesocyclone can potentially be sourced from the lifting and tilting of horizontal vorticity within the inflow layer along the boundaries (e.g., southeasterly change, sea breeze boundary; Markowski et al 1998;Atkins et al 1999). Sills et al 2004 found that low-level boundaries were central to the enhancement and mesocyclone development of storms that produced tornadoes in Sydney under weak synoptic-scale forcing.…”
Section: Environmental Drivers Of Storm Characteristicsmentioning
confidence: 99%